تفسیرِ قرآن کا سائنسی منہج: "کتاب زندگی" کا مطالعہ (Al-Qamar, 2020)
Commentary of the Quran “Kitāb e Zindagī” has been written in the light of scientific discoveries and scientific research. Its writer has been a nuclear scientist. The author has also been the Chairman of the Atomic Energy Commission of Pakistan Yes, this commentary is only the commentary of Surah Al-Imran, Surah Al-Baqarah and Surah Al-Fātihah. Proved to be very useful, one of the purposes of this commentary of the commentator is that the modern people of this society who understand modern science can understand the Quran. The commentator says that in front of me are young people who are so fascinated by the latest discoveries and advances in technology that nations that are not guided by the Quran are developing and Muslims are not involved in this development.
Keywords: Scientific Methodology; Tafsīr; “Kitāb e Zindagī”